Hydrogel Plus as Alternative Technology In Sustainable Palm Oil Agricultural - Mahmudin; Batubara, Muhammad Ilham (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2024)
Palm oil (Elaeis guineensis Jacq.) is one of the most important plantation crops in the agricultural sector. However, during the dry season the production of palm oil is decreasing, due to the reduced availability of water especially on peatlands. One way to overcome this problem is by the use of Hydrogel Plus technology (Hydrogel based bagasse with the addition of Pseudomonas fluorescens). This study aims to determine the role of Hydrogel Plus (Hydrogel with the addition of Pseudomonas fluorescens) to the growth and production of palm oil on the peat during the dry season. The method used in this research is the experimental method using Completely Randomized Design. Treatment was done by 4 treatments and each treatment was repeated 5 times. So the experimental unit amounted to 20 units. The treatments include (P1) Control, (P2) Hydrogel application (P3) Application of Pseudomonas fluoresces suspension and (P4) Hydrogel Plus applications. Based on the result of the research, it can be concluded that Hydrogel administration with the addition of Pseudomonas fluorescens bacteria tends to have a significant effect on leaf diameter, leaf number and height of plant at each treatment and only at plant height on treatment of Pseudomonas fluorescens and only hydrogel treatment which has no effect real utilization of Hydrogel Plus can provide the effect of palm oil plant growth and production to be a specific effort as an alternative technology in sustainable palm oil management in peatlands during the dry season.